The impact of intrapreneurial self-capital on critical thinking and academic engagement among Chinese university students - 賢 渡辺; Jirarat Sitthiworachart; Thanin Ratanaolarn (Cogent Education, 2025)
University students in China face increasing academic demands and pressures, which makes the development of psychological resources, such as resilience, adaptability, and higher-order thinking essential for their success. This study investigates the relationships between Intrapreneurial Self-Capital (ISC), critical thinking dimensions (open-mindedness, systematicity-analyticity, and truth-seeking), and academic engagement among Chinese university students. Using structural equation modeling with partial least squares (PLS-SEM), we assessed the direct effects of ISC on critical thinking and academic engagement, as well as the mediating role of critical thinking dimensions. Data were collected in two waves from a sample of 1043 students, with ISC measured in the first wave and critical thinking and engagement assessed in the second. Results indicate that ISC significantly predicts both critical thinking and academic engagement, and that systematicity-analyticity and truth-seeking mediate this relationship. These findings highlight the central role of critical thinking dispositions in linking psychological resources to students’ academic engagement. Practically, the results suggest that educational practitioners and policymakers could design teaching interventions and training programs that explicitly strengthen ISC and critical thinking to foster deeper academic involvement. The study’s quasi-longitudinal design, reliance on self-report data, and overrepresentation of urban students are noted as limitations.
Keywords: Education and Critical Thinking Development; Higher Education and Employability; Education and Islamic Studies